The Grey Teal at saline drought-refuges in north Queensland - Lavery, H J (Wildfowl, 1972)
Investigations were made of Grey Teal Anas gibberifrons gracilis in north Queensland, particularly at saltwater habitat during 1965-1969. Non-breeding, mainly adult birds utilised saline areas during the annual dry seasons especially in droughts. The sequence of diet imposed by availability and by the birds physiological capabilities, was from brackish-water plant seeds in saltpans, to marine molluscs along open bays. Foods at the ultimate drought-refuge, mostly bivalve molluscs, were of sufficient quantity and quality to bring all birds into extremely good condition. Contact was maintained with freshwater habitat for drinking. Departure from saltwaters was initiated by males after the wet season rainfall; a less strict sequence of decreasingly saline localities was quickly visited during the return to the breeding grounds while gonads of females became active. A preference for freshwater foods, coupled with breeding requirements, enforced departure despite the suitable food supplies still at saltwaters. Use of saline areas for foods resulted in increased ingestion of salts. Functional supraorbital nasal glands provided the chief means of maintaining ionic balance; this physiological adaptation by Grey Teal is modest compared with the complex behavioural changes required of other local waterfowl. The use of saltwater habitat with freshwater contact was facilitated in adults by an adjustable flightless period during the postnuptial moult; the disadvantages of lessened mobility and condition were thus delayed when necessary. Flightlessness during the immature moult was stereotyped and the advantage clearly lay with early-bred birds. The majority of the population of Grey Teal in the region remained in good condition during drought. Mortality of such a highly fecund species was apportioned to late-bred immatures incapable of using saltwater habitat, and to birds returning to breeding grounds over drought-recovering countryside. In north Queensland the general management techniques currently practised during drought to protect waterfowl are adequate for the Grey Teal population; the peculiar habits of this species confer additional insurance against the effects of an essentially arid environment.